Strike-slip fault system and its control on ediacaran hydrocarbon system in central Sichuan Basin: insights from petrology, U-Pb dating and seismic interpretation - Cen, Yongjing; Li, Jianhai; Liang, Feng; Wang, Lien; Zhang, Xin (Frontiers in Earth Science, 2025)
Strike-slip faults are closely related to the enrichment of hydrocarbon resources, with a series of large oil and gas fields associated with strike-slip faults discovered in regions such as the Ordos Basin in China and the West Siberian Basin. The Ediacaran hydrocarbon resources in the Sichuan Basin are abundant. Identifying strike-slip faults and understanding their control over hydrocarbon systems is crucial for expanding exploration efforts. Based on lithology, seismic interpretation, and absolute age data, the strike-slip faults in the Ediacaran system and the overlying strata have been identified and classified. The patterns and evolutionary processes of strike-slip faults have been revealed. The results indicate that the planar patterns of strike-slip faults can be classified into linear, en echelon, and oblique structures. Strike-slip faults are typically seen as vertical (or steep) linear faults or flower-shaped structures in seismic profiles. Vertical (or steep) linear faults can further be categorized into transtensional high-steep structures and transpressional high-steep structures. The evolution of strike-slip faulting in the Central Sichuan Basin can be divided into four distinct stages: (1) a rifting stage during the Cryogenian, (2) a dextral transtensional strike-slip stage from the late Ediacaran to early Cambrian, (3) a dextral, weak transpressional strike-slip stage from the early Ordovician to early Permian, and (4) a sinistral transtensional strike-slip stage during the late Permian to early Triassic. The aulacogen, formed during the Cryogenian, controlled the distribution of the mound-shoal complex of the Dengying Formation and the thickness zones of the Cambrian hydrocarbon source rocks. The strike-slip faults in the first stage facilitated direct lateral and vertical contact between the overlying hydrocarbon source rocks and reservoirs, significantly enhancing the migration and accumulation efficiency of hydrocarbons. The strike-slip faults in the second stage controlled the distribution of ancient sedimentary paleogeomorphology and favorable karst locations. The strike-slip faults in the third stage governed the distribution of gas and water.